THE ROLE OF INTEGRATED CADASTRE DATABASE IN DISASTER RISK MANAGEMENT - Kusmiarto, Kusmiarto (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Due to the complexity of the natural disaster in Indonesia, the effective disaster risk management should have comprehensive information. Cadastre database using parcels as basic mapping units constitute the detailed information related to elements at risk. It is not easy for the institutions in charge with those disaster risk management to access the detailed information. The research is aimed at overcoming the above problems that is by designing the integrated cadastre database scheme. The survey results are use to test the geo-database cadastre scheme. The evaluation is done by in depth interview to the potential users. The result of evaluation showed that the cadastre database made is good enough to solve the above mentioned problems. Keywords: cadastre, design, geo-database, elements at risk, earthquake.